Converge : 21st century literature from the philippines and the world - Raquitico, Kornellie I.; Raquitico,Kornellie I.; Perez, Frances Paola D. (Quezon City, Philippines : Phoenix Publishing House Inc., 2019)
Writing poetry
Creating the self -- Conflicting interests -- Cutting edges Crossing thresholds -- Attaining lifee goals -- making life-changing decisions -- Crossing borders -- Engaging in human/e pursuits
Literature
includes bibliographic references and index.
English
Keywords: Literature from the philippines